Tawhid, Environment, and Humanity: Islamic Education Values in Sapta Darma Teachings - Rochmad Rochmad; Mahmutarom Mahmutarom; Sari Hernawati (Universitas Wahid Hasyim Semarang, 2025)
Abstract This study aims to analyze the application of Sapta Darma Spiritual Values (KSD) in the perspective of Islamic Education in Kendal Regency, which is known for its religious and social diversity. The diversity of religions in Indonesia, including local beliefs such as Sapta Darma, shows relevance in shaping the social and moral character of the community. This study uses a qualitative approach with ethnographic methods, where data is collected through in-depth interviews, observations, and literature studies. The purposive sampling technique was applied to select five informants who adhered to the Sapta Darma sect. The results of the study show that the teachings of KSD, which emphasizes values such as monotheism, ethics towards nature, and integration with Islamic educational values, are in line with Islamic moral principles. KSD plays a role in building social harmony, ethical awareness, and tolerance between religious communities in Kendal Regency. In addition, values such as courage, patience, individual freedom, and concern for the common good taught in KSD contribute to the formation of strong and responsible character. These findings affirm the importance of integrating local and spiritual teachings in Islamic education to strengthen the spiritual and moral identity of Indonesian society. This research fills a gap in the understanding of the synergy between Islamic education and local teachings, especially in forming a more harmonious and integrity society Keywords: Analysis, Values, Sapta Darma, Islamic education